2017
DOI: 10.1080/09513590.2017.1415676
|View full text |Cite
|
Sign up to set email alerts
|

Dienogest treatment after ovarian endometrioma removal in infertile women prior to IVF

Abstract: Background: Severe forms of genital endometriosis are known to be associated with infertility and its subsequent treatment failure. Both gonadotropin-releasing hormone analogs (a-GnRH) and dienogest have been suggested as additional hormone therapy for patients with endometriomas. However, the result of hormonal suppression before an in vitro fertilization (IVF) cycle remains undetermined. Materials and methods: A prospective cohort study of 144 infertile women planning IVF after laparoscopic surgery of ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…36,38 Surgical approach was by laparoscopy (n=13), 15,26–33,39–42 laparotomy (n=3), 34,36,38 or either one (n=3). 14,35,37 Four trials 28,31,40,41 included only patients with American Society for Reproductive Medicine Revised Classification of Endometriosis 21 stage 1 or 2, seven trials 15,29,30,32,34,37,38 included only patients with stage 3 or 4, and eight trials 14,26,27,33,35,36,39,42 included all stages. In seven trials, 14,29,30,32,36,39,42 only a subgroup of patients attempted pregnancy after surgery and were included in the analyses.…”
Section: Resultsmentioning
confidence: 99%
“…36,38 Surgical approach was by laparoscopy (n=13), 15,26–33,39–42 laparotomy (n=3), 34,36,38 or either one (n=3). 14,35,37 Four trials 28,31,40,41 included only patients with American Society for Reproductive Medicine Revised Classification of Endometriosis 21 stage 1 or 2, seven trials 15,29,30,32,34,37,38 included only patients with stage 3 or 4, and eight trials 14,26,27,33,35,36,39,42 included all stages. In seven trials, 14,29,30,32,36,39,42 only a subgroup of patients attempted pregnancy after surgery and were included in the analyses.…”
Section: Resultsmentioning
confidence: 99%
“… 2 In an RCT, which compared 6 months of administration of dienogest (2 mg/day) and triptorelin (3.75 mg/month) to no treatment, the dienogest group had significantly higher pregnancy rate and delivery rate compared to the non‐treatment group (44.7% vs. 16.7% and 36.8% vs. 11.1%, respectively), while the triptorelin group did not have significant differences with the no‐treatment group. 3 In addition to these studies, a Chinese group published a protocol for and began an RCT involving 1–2 months of GnRH agonists in 2018, 4 while a Dutch group published a protocol for and began an RCT involving 6 months of OCs/LEPs or GnRH agonists in 2019 5 ; reports of results from these RCTs are awaited. Although not a hormone preparation, an RCT reported that the PPAR‐γ agonist, pioglitazone, during the ovarian stimulation cycles resulted in significantly higher implantation rates than in patients who did not receive pioglitazone.…”
Section: Cq 13 Are Hormone Therapies Effective For Endometri...mentioning
confidence: 99%
“…All of the women had undergone laparoscopic surgery for ovarian endometriomas previously. Women who received DNG pretreatment had a 2.5-fold higher clinical pregnancy rate (44.7% versus 16.7%, p = 0.012), and a three-fold higher delivery rate (36.8% versus 11.1%, p = 0.013) than controls [ 55 ].…”
Section: Reproductive Outcomes After the Treatment Of Adenomyosismentioning
confidence: 99%